Surgical treatment of hyperparathyroidism secondary. Preliminary results of cryopreserved glandular tissue viability - Lista, Ricardo; Sueta, Patricia; Pérez Campo, Héctor; Saldías, María del Carmen; Ruiz, Andrea (Cirugía del Uruguay, 2004)
Case material consists of the preliminary results regarding 20 patients operated in Surgical Clinic F of the University Hospital from 1999 through 2001, with diagnosis of secondary hyper parathyroidism. The patients were subje ct to subto ta/ parathyroidectomy, with cryo-preservation of resected gland parenchyma. Consequent thereto the authors review existing bibliography on this condition.